2014
DOI: 10.1155/2014/286170
|View full text |Cite
|
Sign up to set email alerts
|

Selective Depletion of Regulatory T Cell Subsets by Docetaxel Treatment in Patients with Nonsmall Cell Lung Cancer

Abstract: Regulatory T (Treg) cells are potent suppressors that maintain immune homeostasis. Accumulation of Treg can inhibit effective immune responses in cancer patients, leading to tumor development and progression. Despite direct cytotoxicity, several chemotherapeutic drugs have been reported to deplete Treg cells for better prognosis for cancer patients. Treg cells are a heterogenous population with at least three different subsets, nonsuppressive, resting, and activated Treg cells. However, the characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 36 publications
(38 reference statements)
4
107
0
8
Order By: Relevance
“…3,4 Patients with cancer are more susceptible to infection than individuals without cancer because of their systemic immunosuppressive state caused by the malignancy and anticancer treat ments, such as chemotherapy or surgery. [5][6][7][8] Therefore, these patients might be at increased risk of COVID-19 and have a poorer prognosis.…”
mentioning
confidence: 99%
“…3,4 Patients with cancer are more susceptible to infection than individuals without cancer because of their systemic immunosuppressive state caused by the malignancy and anticancer treat ments, such as chemotherapy or surgery. [5][6][7][8] Therefore, these patients might be at increased risk of COVID-19 and have a poorer prognosis.…”
mentioning
confidence: 99%
“…Docetaxel treatment reduced numbers of in vitro Treg cells originally obtained from NSLC patients [89]. In this study, two subsets of Treg cells were found where one Treg subset secreted more IFN-Îł and less TGF-ÎČ.…”
Section: Th1 and Th2 Cells In Immune Modulationmentioning
confidence: 59%
“…Multiple chemotherapeutics including cyclophosphamide, docetaxel, gemcitabine, vinorelbine, and cisplatin have been shown to deplete tumor‐infiltrating T REG cells in vivo, especially when administered according to metronomic regimens . A single dose of cyclophosphamide improved therapeutic responses, delayed time to recurrence, and boosted the establishment of immunological memory in a mouse model of breast cancer co‐treated with RT and the Toll‐like receptor 7 (TLR7) agonist imiquimod .…”
Section: Strategies To Improve Immunostimulationmentioning
confidence: 99%